1984
DOI: 10.2135/cropsci1984.0011183x002400060037x
|View full text |Cite
|
Sign up to set email alerts
|

CO2‐Enrichment Effects on Wheat Yield and Physiology1

Abstract: High CO2 was applied to field‐grown winter wheat (Triticum aestivum L. cv. Arthur) during different growth periods in order to identify when photosynthesis was most limiting grain yield. Wheat was grown in open top Mylar® polyester chambers which were provided with circulated air (340 μL/L CO2 = control treatment) or air enriched with sufficient CO2 to expose the foliage to 1200 μL/L (high CO2 treatment). The CO2 enrichment treatments were applied from jointing to anthesis, from jointing to maturity, or from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
24
1
1

Year Published

1986
1986
2002
2002

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(33 citation statements)
references
References 0 publications
7
24
1
1
Order By: Relevance
“…In older (4 week old) wheat plants we have found much larger starch deposits in tissue grown in elevated CO 2 (data not shown). These observations indicate that a shift in the source-sink status occurs in the older plant and leads to an accumulation of starch in the elevated CO 2 -grown leaf tissue as previously found in the other mature plants (Cave et al, 1981;Havelka et al, 1983;Vu et al, 1989;Yelle et al, 1989;Lawlor and Mitchell, 1991 …”
Section: Oec33supporting
confidence: 74%
See 1 more Smart Citation
“…In older (4 week old) wheat plants we have found much larger starch deposits in tissue grown in elevated CO 2 (data not shown). These observations indicate that a shift in the source-sink status occurs in the older plant and leads to an accumulation of starch in the elevated CO 2 -grown leaf tissue as previously found in the other mature plants (Cave et al, 1981;Havelka et al, 1983;Vu et al, 1989;Yelle et al, 1989;Lawlor and Mitchell, 1991 …”
Section: Oec33supporting
confidence: 74%
“…There have been several studies of the effects of elevated CO, on the growth of the wheat crop and its physiology (for reviews, see Lawlor and Mitchell, 1991;Long and Drake, 1992), and it is well established that increasing CO, levels can affect leaf growth and photosynthetic rates in wheat plants that are several weeks old (Akita and Moss, 1972;Neales and Nicholls, 1978;Havelka et al, 1983;du Cloux et al, 1989;Chaudhuri et al, 1990;Lawlor and Mitchell, 1991). Many of the effects on growth in elevated CO, may be secondary, since the initial response of the plant to elevated CO, is elicited immediately after atmospheric CO, is sensed by the plant.…”
Section: ~ ~~ ~~mentioning
confidence: 99%
“…In wheat grown at [C02]7oo, foliar starch and sucrose were elevated in flag leaves until seed filling began; glucose levels were little altered (Havelka et al 1984). In A. sativa, we found that starch levels rose, dusk sucrose levels increased somewhat, and pre-dawn fructose fell with CO2 enrichment (Fig.…”
Section: Carbohydrate Pools and Exportmentioning
confidence: 58%
“…It is possible that faster rates of cell division at high CO, are not only important during vegetative shoot initiation in the apex but also during grain initiation in the panicle and endosperm development in the grain. The importance of timing of exposure to elevated CO, in obtaining a yield increase at high CO, was also demonstrated by Havelka et al (1984) using wheat. When plants were exposed to high CO, during grain initiation, there was an increase in yield; however, there was no response to high CO, when plants were exposed to high CO, during grain filling only.…”
Section: Long-term Effects Of Early Changes In the Shoot Apex At Highmentioning
confidence: 95%